HUBUNGAN INTERNAL LOCUS OF CONTROL DENGAN FEAR OF SUCCESS PADA POLISI WANITA YANG SUDAH MENIKAH DI MAPOLDA JAWA TENGAH - Marita Riantika; Alice Zellawati; Brigitan Argasiam (IMAGE, 2021)
This research aims to determine the relationship between internal locus of control and Fear of Success among married female police officers in MAPOLDA Central Java. The population in this study were all female police officers who were married and served at the Central Java Regional Police Headquarters, totaling 115 people with a sample of 78 married female police officers at the Central Java Regional Police Headquarters. The sampling technique uses incidental sampling technique. This research uses a psychological scale data collection method in the form of a Likert scale which consists of two scales, namely, the internal locus of control scale with 28 items (? = 0.900) and the Fear of Success scale with 24 items (? = 0.899). Based on the hypothesis proposed in this research, namely: "There is a relationship between internal locus of control and fear of success", indicating that the hypothesis can be accepted. This is shown by the value of rs = - 0.880 with p = 0.000 (p < 5%) meaning "The higher the internal locus of control the individual has, the lower the fear of success in the individual, conversely the lower the internal locus of control the individual has, the The lower the fear of success in the individual." The effective contribution value of the internal locus of control variable to the fear of success is 74.9%, while most of the peace, namely 25.1%, is influenced by other factors. Keywords: internal locus of control, fear of success